A Concise and Efficient Total Synthesis of Militarinone D. Issue 18 (15th May 2015) - Dash, Uttam; Sengupta, Sandip; Sim, Taebo
Abstract: A highly stereoselective, concise (14 steps longest linear sequence and 20 steps overall), and efficient (15 % overall yield) synthesis of militarinone D has been accomplished. The key reactions utilized in the sequence are enzymatic desymmetrization, cis / trans isomerization, Horner–Wadsworth–Emmons olefination, and addition of an organolithium species to a highly conjugated chiral aldehyde. The simplicity of the strategy may enable its utilization in the large‐scale production of this target. Moreover, the strategy utilized to design the route should be applicable to the preparation of analogs that bear a variety of substituted pyridinone core structures. Abstract : A highly efficient (15 % overall yield) and convergent (longest linear sequence of 14 steps) synthesis of militarinone D from a known intermediate has been accomplished.